The Affordable Care Act, Insurance Coverage, and Health Care Utilization of Previously Incarcerated Young Men: 2008–2015 - Winkelman, Tyler N. A. (Am J Public Health, 2017)
Objectives. To estimate health insurance and health care utilization patterns among previously incarcerated men following implementation of the Affordable Care Act’s (ACA’s) Medicaid expansion and Marketplace plans in 2014. Methods. We performed serial cross-sectional analyses using data from the National Survey of Family Growth between 2008 and 2015. Our sample included men aged 18 to 44 years with (n = 3476) and without (n = 8702) a history of incarceration. Results. Uninsurance declined significantly among previously incarcerated men after ACA implementation (–5.9 percentage points; 95% confidence interval [CI] = −11.5, –0.4), primarily because of an increase in private insurance (6.8 percentage points; 95% CI = 0.1, 13.3). Previously incarcerated men accounted for a large proportion of the remaining uninsured (38.6%) in 2014 to 2015. Following ACA implementation, previously incarcerated men continued to be significantly less likely to report a regular source of primary care and more likely to report emergency department use than were never-incarcerated peers. Conclusions. Health insurance coverage improved among previously incarcerated men following ACA implementation. However, these men account for a substantial proportion of the remaining uninsured. Previously incarcerated men continue to lack primary care and frequently utilize acute care services.